Pengaruh Pelatihan dan Lingkungan Kerja Terhadap Kinerja Karyawan Lariz Depari Hotel Medan - Bungaran Siallagan; Miftahuddin Miftahuddin; Isnaniah LKS (Universitas Medan Area, 2020)
The purpose of this study was to determine the effect of training and work environment partially on the performance of Lariz Depari Hotel Medan employees and to determine the effect of training and work environment simultaneously on the performance of Lariz Depari Hotel Medan employees. This type of research is associative. The population in this study were employees of Lariz Depari Hotel Medan for two months of research using a sample of 45 people. Data collection techniques using a questionnaire or questionnaire. The data analysis technique used is a statistical test that uses multiple linear regression analysis, F test, t test, and test of determination using SPSS Software for 21.00.The results of the study using the statistical test of t are known that the training variable (X1) partially has a positive and significant effect on employee performance (Y) that is obtained tcount ttable (6.258 2.018) with a significance level of 0,000 0.05 and work environment variables (X2) partially positive and significant effect on employee performance (Y) is obtained tcount t table (4,400 2.018) with a significant level of 0,000 0.05. The results of the F test for training variables (X1) and work environment (X2) can be concluded that the training variables (X1) and work environment (X2) simultaneously have a positive and significant effect on employee performance (Y) that is obtained Fcount Ftable (47.572 3.22) with a significant level of 0.000 0.05.